The question of plurality and universal affirmation: A dialogue of thought between Arendt and Badiou - Akin, Zanan (HannahArendt.net, 2024)
Both Hannah Arendt and Alain Badiou refer to a ‘disorientation of the world’ in different moments of their oeuvre. For Arendt, a disorientation emerges if the common sense dissolves; for Badiou, if there is an absolute primacy of negation and an inability to affirm anything universal. This paper takes current protest movements as a serious symptom of a disorientation in the sense of both thinkers. For it seems that today far from affirming any universal point, ‘protests’ seem to turn into ‘contests’ of ‘being against’. Conceptualized as a dialogue of thought between Hannah Arendt and Alain Badiou, the paper aims to reveal a profound crisis behind this symptom, that is a critical tension between two concurrent promises of modern democracy, namely ‘equality’ and ‘right to difference’. In that frame, the paper tries to think a renewed politics of equality which can affirm plurality and difference without falling either into indifference of being the same species or into the cult of ‘me’ that is a fantasy of absolute difference.